Is There Room for the Other in a “Modernized” Education? - Heringer, Rebeca; Janzen, Melanie (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
The enactment of the Education Modernization Act by the government of Manitoba in early 2021 proposed several structural changes to the governance and delivery of provincial education. The related documents had a strong emphasis on improving the achievement of all students, making them future-ready and strengthening parental involvement. Despite potentially relevant claims of equity and diversity promotion, in this paper we discuss how the government discourse is neither modern nor necessarily better, as it claims to be. Rather, the proposed Education Modernization Act reifies mainstream worldviews and ideas that have been proclaimed since the beginning of the 20th century and which are today empowered by a global neoliberal mindset. We conclude arguing that a non-totalizing response to the Other is a necessary and yet missing disposition in any genuine social justice education.